The Application of Authentic Assessment to Improve the Learning Outcomes of Science in the fourth-grade students of SD Negeri 2 Pupuan - Arta Eka Wiana, Pt. Juny; Gading, I Ketut; Kusmariyatni, Nyoman (LPPM Undiksha, 2017)
This study is aimed at improving students’ learning outcomes in science in the fourth grade of SD Negeri 2 Pupuan District Tegallalang, Gianyar in the academic year of 2014/2015 after the implementation of authentic assessment. This research is a classroom action research conducted in two cycles. Each cycle consisted of four stages, namely planning, action, observation/ evaluation, and reflection. The subjects were students of class IV SD Negeri 2 Pupuan District Tegallalang, Gianyar in the academic year 2014/2015 which amounted to 15 people, consisting of 8 boys and 7 girls. The data of the learning outcomes were obtained by using the test method and analyzed with descriptive statistical analysis techniques. The results of this study were found that the application of authentic assessment can improve students’ learning outcomes in science in the fourth grade of SD Negeri 2 Pupuan District Tegallalang, Gianyar 2014/2015 with an average score of learning outcomes at the end of the first cycle reached 62.27 belonged to enough category and the average score of learning outcomes at the end of the second cycle reached 69.33 which was located in the good category.